Broad considerations concerning electrochemical electrodes in primarily fluid environments. - Jesudason, Christopher G (MDPI, 2009)
This review is variously a presentation, reflection, synthesis and report with reference to more recent developments of an article - in a journal which has ceased publication - entitled "Some Electrode Theorems with Experimental Corroboration, Inclusive of the Ag/AgCl System" Internet Journal of Chemistry, (http://www.ijc.com), Special Issues: Vol. 2 Article 24 (1999). The results from new lemmas relating charge densities and capacitance in a metallic electrode in equilibrium with an ionic solution are used to explain the data and observed effects due to Esin, Markov, Grahame, Lang and Kohn. Size effects that vary the measured e.m.f. of electrodes due to changes in the electronic chemical potential are demonstrated in experiment and theory implying the need for standardization of electrodes with respect to geometry and size. The widely used Stern modification of the Gouy-Chapman theory is shown to be mostly inapplicable for many of the problems where it is employed. Practical consequences of the current development include the possibility of determining the elusive single-ion activity coefficients of solution ions directly from the expression given by a simplified capacitance theorem, the potential of zero charge and the determination of single ion concentrations of active species in the electrode reactions from cell e.m.f. measurements.